Lingual accessory mental foramen: a report of an extremely rare anatomical variation - Neves, Frederico S.; Torres, Marianna G. G.; Oliveira, Christiano; Campos, Paulo S. F.; Crusoé-Rebello, Iêda (Journal of Oral Science, 2010)
The presence of accessory foramina and canals in the mandible is frequently overlooked in clinical procedures. It is important to note that these anatomical variations may only be pre-surgically detected on imaging exams, and such detection may directly influence therapeutic success. We describe a previously unreported case of accessory mental foramen located in the lingual cortical bone of the mandible. (J Oral Sci 52, 501-503, 2010)